(untitled) (Panacea Journal of Medical Sciences, 2022)
Introduction: Tonsillectomy is one of the leading surgical operations of the ENT profession. Chronic tonsillitis has a massive effect on the quality of life and tonsillectomy used to treat the disease is a major procedure that can lead to multiple intraoperative and post-operative conditions, including bleeding, discomfort, etc., resulting in lack of school/work and impaired quality of life. Aim: To study the outcome of surgical procedures between CO2 laser Tonsillectomy and conventional tonsillectomy. Materials and Methods: In this study, 50 patients with chronic tonsillitis were included and randomized to underwent one tonsil removal by CO2 Laser method and the other side by Conventional dissection method. The outcome of the two procedures was measured using the duration of surgery, blood loss on each side. Post-operative bleeding, pain and tonsillar fossa healing were evaluated on the first, second and seventh day. Results: The duration of surgery in the C02 laser method was 11.8±3.65 minutes, and the conventional method was 16.4±4.66 minutes. (P <0> Conclusion: CO2 Laser tonsillectomy is a simple procedure that results in substantially less intraoperative blood loss, post-operative discomfort, and a shorter surgery time.